Performance Analysis of M2M Sensor Networks. (18th May 2016) - Wang, Jingjing; Xu, Lingwei; Dong, Xinli; Shi, Wei; Niu, Qiuna
Abstract : The average symbol error probability (ASEP) and outage probability (OP) performance of mobile-to-mobile (M2M) senor networks employing transmit antenna selection (TAS) and selection combining (SC) over N -Nakagami fading channels are investigated in this paper. Based on the moment generating function (MGF) approach, the exact ASEP expressions are derived for several modulation schemes. The exact closed-form OP expressions are also presented. Then, the ASEP and OP performance under different conditions are evaluated through numerical simulations to confirm the accuracy of the analysis. The simulation results show that the number of antennas, the fading coefficient, and the number of cascaded components have an important influence on the ASEP and OP performance.